The concept of an integrated rail transit system based on tram-trains in the metropolitan area on the example of Piaseczno - Wontorski, Paweł (Przegląd Komunikacyjny)
The article presents the concept of an integrated rail transit system for Piaseczno, which is one of the main urban centers of the Warsaw Metropolitan Area. The conditions for the development of new lines and the use of existing infrastructure were analyzed. An agglomeration rail transit system based on normal and narrow gauge railways and tram-train was proposed, taking into account the stages of network development and integration of various modes of transport. The proposed solution can be a model for the development of rail transport in the metropolitan area. Keywords: Tram-train; Narrow-gauge railway; Piaseczno